Implementation of Inclusive Education for Children with Deaf Special Needs in Elementary Schools - Ramadhan, Aldy Tri; Rahmania, Intan Putri; Nazarina, Vera Dewi; Arifin, Achmad Januar (International Conference on Elementary Education, 2025)
Inclusive education provides opportunities for individuals with special needs to learn in the same environment and develop their potential. Deaf children, who have hearing limitations, are an example of children with special needs (CWSN) requiring education alongside their peers. This study aims to describe the implementation, barriers, and evaluation of inclusive education for deaf children in elementary schools. Using a library research method, data were collected from various literary sources such as relevant journal articles. The study reveals that inclusive education for deaf children in Indonesian elementary schools involves structured planning, implementation, and evaluation stages. In the planning stage, teachers prepare a general syllabus and Lesson Plan (RPP), adjusted to the needs and abilities of deaf children through an Individualized Education Program (IEP). Barriers include limited teacher time for special planning, communication difficulties, and managing the emotions of deaf children. To address these challenges, schools need better facilities and resources, such as acoustically friendly classrooms and visual and audio aids.